The Administration of Topical Aloe vera Extract Reduce the Number of Sunburn Cells and Expression of Caspase-3 on Post UVB-light-exposure Epidermis - Soetrisno, Kusumawati; Subchan, Prasetyowati; Hussana, Atina (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2020)
Introduction: Ultraviolet B (UVB) radiation triggers the formation of free radicals that cause apoptosis and sunburn cells (SBC) formation. Aloe vera contains anti-inflammatory and antioxidant compounds that can potentially inhibit this process. Objective: to assess the effect of topical Aloe vera extract administration on the decrease of SBC number and Caspase-3 expression on the epidermis after UVB light exposure.Methods: In a post-test only group design study, a single dose of 3 doses of Erythema (DEM) was performed on two groups of 6 week old BALB/c female rats. Group A (control) did not receive any topical treatment, and group B (treatment) were smeared with 75% Aloe vera extract before irradiation. Each group was divided into 4 sub-groups based on post-exposure time of 6 hours (A1 and B1), 12 hours (A2 and B2), 24 hours (A3 and B3), and 48 hours (A4 and B4). The expression of caspase-3 was assessed by immunohistochemical staining while the SBC number was measured using a microscope. The expression of caspase-3 was analyzed using the Kruskal-Wallis and Mann-Whitney statistical tests, while the number of SBC was analyzed using the one-way ANOVA statistical test and the post-hoc LSD test.Results: The results of the Kruskal-Wallis analysis showed a significant difference in Caspase-3 expression between groups, p <0.05. The results of Mann-Whitney analysis showed a significant difference in Caspase-3 expression between the A1-A3 and B1-B3 subgroups (p <0.05). One-way ANOVA analysis showed a significant difference in the number of SBC between groups (p <0.05). Post-hoc LSD analysis showed significant differences in SBC counts between groups A and B across all subgroups, p <0.05.Conclusion: Topical application of Aloe Vera extract decreased Caspase-3 expression and the number of SBC in UVB light-exposed skin.